2004
DOI: 10.1063/1.1801159
|View full text |Cite
|
Sign up to set email alerts
|

The growth and optical properties of large, high-quality AlN single crystals

Abstract: The effect of impurities and defects on the optical properties of AlN was investigated. High-quality AlN single crystals of more than 20mm2 size were examined. Different crucible materials and growth procedures were applied to the growth of bulk AlN by physical vapor transport method to vary the defect and the impurity concentrations. The crystalline orientation was investigated by Raman spectroscopy. Glow discharge mass spectrometry was used to determine the trace concentration of the incorporated impurities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
63
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 53 publications
10
63
0
1
Order By: Relevance
“…For example, in Ce doped garnets, the range of peak positions is in the 500-550 nm range. 1 Since, consistent with previous studies, [22][23][24][25] the un-doped AlN (sample 7) does not show the 490 nm peak, we attribute the deconvoluted peak centered at 490 in Ce:AlN to the 4f to 5d electronic transitions of the Ce 3+ dopant.…”
Section: -5supporting
confidence: 66%
See 1 more Smart Citation
“…For example, in Ce doped garnets, the range of peak positions is in the 500-550 nm range. 1 Since, consistent with previous studies, [22][23][24][25] the un-doped AlN (sample 7) does not show the 490 nm peak, we attribute the deconvoluted peak centered at 490 in Ce:AlN to the 4f to 5d electronic transitions of the Ce 3+ dopant.…”
Section: -5supporting
confidence: 66%
“…PL caused by intrinsic defects such as vacancies, O impurities, and their complexes in AlN is well known. [22][23][24][25] AlN is extremely susceptible to O contamination, so O impurities are typically considered intrinsic. Studies on AlN ceramics 22,23 observed a PL peak in the ∼300 to 375 nm region and attributed it to an O related defect complex [V A1 -O N · ].…”
Section: -5mentioning
confidence: 99%
“…It shifts from 3.3 to 4.0 eV with the oxygen concentration as reported. 20 The nitrogen vacancy and Al interstitial point defects are responsible for the visible emission as suggested by Strassburg et al 21 Unlike the extremely broadband emission from AlN, 22,23 the FWHM of the emissions of AlN nanorods is about 15 and 70 nm, corresponding to UV and visible emission, respectively. The PL measurement provides strong evidence for the existence of a shortening phonon lifetime mechanism via impurities and defects.…”
mentioning
confidence: 96%
“…Another kind of the two-stage procedure was reported by M. Strassburg et al (Strassburg et al, 2004) where the temperature was gradually ramped between the two stages and by Z. Sitar et al (Sitar et al, 2004) who used vaporization of Al (use of the metal vapour source is called direct synthesis method by K. Nishino et al (Nishino et al, 2002)) 13 at the first and the AlN powder source at higher temperature at the second stage; two-stage growth was also used by R. Dalmau et al with stages differing in the growth temperature and, thus, growth rate.…”
Section: Experimental Set Up For Aln Bulk Growthmentioning
confidence: 99%